Various Carbon Nanomaterials (CNMs) synthesized on powdered activated carbon by CVD reactor - AlSaadi, Mohammed A.; Al-Mamun, Abdullah; Muyibi, Suleyman Aremu; Alam, Md. Zahangir; Sopyan, Iis; Ahmed, Yehya M.; Atieh, Muataz A. (2011)
Synthesis and characterization of composite carbon nanomaterials (CNMs) are reported in this paper. Carbon nanomaterials are produced on oil palm shell powdered activated carbons (PACs), which were impregnated with iron (Fe) catalysts, with the help of sonication bath. Chemical Vapor Deposition (CVD) of C6H6 and C2H2 were used in the presence of hydrogen at various temperatures (ºC). The flow rates of carbon source and hydrogen were varied to study the effect on the types of CNMs. The CNMs were formed directly on the surface of the impregnated PAC, resulting in cleaner production compared to floating catalyst method. Variable weight percentage (1, 3, 5, and 7%) of the catalyst salt (Fe+3) were used for the impregnation. However, the best catalysis was observed on the substrate with 5% Fe+3. The product displayed a relatively high surface area, essentially constituted by the external surface. New functional groups were also appeared compared to those in the PAC. Field Emission Scanning Microscopy (FESEM), Transmission Electron Microscopy (TEM), Fourier Transform Infrared (FTIR) and Energy Dispersive X-ray (EDX) were used for the characterization of the new carbon nanoproduct, which was produced through a clean novel process.